CO2 capture and conversion: A homemade experimental approach - Adalberto Acuña-Girault; Ximena Gómez del Campo-Rábago; Marco Antonio Contreras-Ruiz; Jorge G. Ibanez (OmniaScience, 2022)
During the SARS-2-Covid pandemic our institution sought to continue the teaching and learning of experimental laboratories by designing, assembling, and delivering a microscale chemistry kit to the students´ homes. Thanks to this approach students were able to perform ~25 experiments during each one of the Fall 2020 and Spring 2021 semesters in an elective Electrochemistry and Corrosion course offered to Chemical Engineering undergraduates. In addition to performing traditional experiments, students were encouraged to design some of their own and have the entire group reproduce them. One of such student-designed experiments involved the capture of CO2 and its reduction with a readily available active metal (i.e., Al foil) in aqueous media to generate potentially useful products. The highly negative standard potential of Al is exploited for the reduction of lab-generated CO2, and the products are chemically tested. Al as a foil has been reported to be electrochemically inactive for carbon dioxide reduction. However, encouraged by an earlier report of the reduction of CO2 to CO, the Al surface is activated in the present experiment by removal of its natural oxide layer with a solution of CuCl2 produced in an electrochemical cell. This procedure enables Al to react with CO2 and yield useful chemistry. This experiment turned to be a discovery trip. The detailed procedure is discussed here, as well as the teaching methodology, grading scheme, and student outcomes.